Trinity Long Room Hub Arts and Humanities Institute Annual Report 2017-18 - Johnson, Emily; King, Aoife; Curtis, Caitriona (Trinity College Dublin, 2018)
The Trinity Long Room Hub Arts and Humanities Research Institute Annual Report covers the actions, achievements and impact of the Research Institute and its hosted projects in the academic year 2017-18.
PUBLISHED
This report covers the activities of the Trinity Long Room Hub Arts and Humanities Research Institute and its hosted projects with respect to research and public humanities programming drawing on Arts and Humanities expertise to tackle complex societal challenges. This includes but is not limited to reporting on the impact of BREXIT on Research and Education; the SHAPE-ID project (Shaping interdisciplinarity in Europe); the role of charismatic leaders in changing the path of history ("Sometimes it matters who is in power" The Annual Edmund Burke Lecture); Genocide and Ethnic Cleansing in our Times (among other Behind the Headlines public discussions); Factions, Fears and Fake News (a symposium in collaboration with Columbia University's Heyman Centre); a global project on the Crises of Democracy supported by the Mellon Foundation.
Keywords: Arts and Humanities; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Identities in Transformation; Inclusive Society; International Development; International Integration; Making Ireland; Manuscript, Book and Print Cultures